El camino del santazo. La narrativa del padecimiento misionero en Urabá, Colombia (2004)
ABSTRACT: This paper addresses the last seven years of the life of barefoot carmelite missionary, Jose Joaquin Arteaga, Director of the Apostolic Prefecture of Uraba, a zone between Antioquia and Choco, in Northwestern Colombia, from 1919 to 1926. It examines his constant movement between duty and claims for improved health conditions, already deteriorated by accidents and tropical disease. Overwhelmed by the inhospitable nature of Uraba, Arteaga and his missionaries were forced abandon the mission in 1921. The article examines the various reactions to this abandonment in Colombia, Spain, and the Vatican, as well as their consequences on the prefect’s biography. The rediscovery of the existential dimension of illness allows for a detailed approach into the biography of missionary suffering, generally examined by scholars as collective actors rather than as individuals.